Application of strip domain and parabolic region on univalent holomorphic functions - Najafzadeh, Shahram (Al-Qadisiyah Journal of Pure Science, 2021)
In this paper, by using univalent functions connected with the strip domain, parabolic starlike and parabolic uniformly convex functions are introduced. Some relations between these classes are proved.